Action Research for Developing Teachers’ Pedagogical Skills in the ‘Out of School Children Education Program’ (Teacher’s World: Journal of Education and Research, 2024)
This study aimed to investigate the potential influences of action research on the professional development of teachers involved in the ‘Out of School Children (OSC) Education Program’ in Bangladesh. The qualitative approach was used with an action research component. Seventeen teachers from seventeen non-formal schools (learning Centers) from eight divisions were selected purposively. Semi-structured interviews, class observations, reflective diaries, and field notes were used to gather data. The thematic technique of qualitative data analysis was utilized. The results show that although every teacher from the seventeen learning centers engaged in very impromptu activities, their teaching-learning strategies were restricted to a few common exercises like group work, peer work, storytelling, reading aloud to each other while adhering to the teacher's instructions, and Club Day activities. The usual pedagogies of the learning centers were reciting the Quran together, singing the national anthem, and taking oaths. The results also show that teachers could reflect on their current pedagogical practices and create professional development strategies through a well-run collaborative action research project. The action research also revealed some noteworthy modifications of pedagogical practices. Numerous obstacles have been discovered and discussed. The results have implications for non-formal education research, practice, and policy. Even if the results of this qualitative research cannot be broadly applied because of its nature, there are instances where the process of implementing changes via an adaptable and tailored kind of action research could serve as a powerful model in a non-formal education setting. The results will also add to the body of knowledge in the fields of non-formal education, teacher preparation, and, more especially, the development of pedagogical skills in non-formal school teachers.Teacher’s World: Journal of Education and Res arch, 50(1): 61-78